The Effect of HLA-DRB1 Allele Mismatch on the Results after Hematopoietic Stem Cell Transplantation - Mats, Remberger; Jonas, Mattsson (Journal of Bone Marrow Biology, 2017)
This article examines how HLA‑DRB1 allele mismatching influences outcomes after hematopoietic stem cell transplantation. It reviews graft‑versus‑host disease risk, engraftment, and survival metrics in the context of donor matching strategies. The findings support careful allele‑level typing to optimize donor selection and improve post‑transplant prognosis.
Keywords: HLA-DR; ATG; relapse; HSCT.